Critical Review of Literature on Enterprise Risk Management and the Cost of Capital: The Value Creation Perspective - Fong-Woon, Lai; Noor Azlinna, Azizan (Academic Journals, 2012)
Enterprise risk management (ERM) encompasses the spectrum of identifying and analyzing risk from an integrated, company-wide perspective in a structured and disciplined approach in aligning strategy, processes, people, technology and knowledge with a purpose of evaluating and managing the uncertainties facing the enterprise as it creates value. ERM essentially lays concern for managing the firm’s idiosyncratic risks apart from the systematic risks. However, the neo-classical finance theory (NCFT) postulates that managing the firm’s idiosyncratic risks is irrelevant. ERM implementation framework embraces the active management of the firm’s three classes of unsystematic risk, namely tactical risk, strategic risk and normative risk. This paper aims to provide a critical review of literature on the notion of managing firms’ unsystematic (specific) risk via an ERM implementation framework that leads to the enhancement of shareholders’ value. The mechanism through which the firms’ value enhancement is supposed to take place is theorized by a strategic conceptualization of risk premium model.